ARTIFICIAL INTELLIGENCE IN EDUCATION: CHALLENGES AND OPPORTUNITIES - Andrei Komissarov (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Artificial Intelligence (AI) has become the most talked-about term of the year. However, in education—as in any knowledge-intensive field—its application is far from straightforward. While large language models, now widely used across industries, often produce “hallucinations” or inaccurate responses, such shortcomings are unacceptable in educational settings. So, how can we develop AI tools that genuinely address the challenges of modern education, ease the workload of teachers and students, enhance learning effectiveness, and, most importantly, make education more personalized? What AI approaches can be truly helpful for educators in their daily practice? In this talk, we will explore these questions and also examine successful case studies of AI implementation in higher education across Eastern Europe.